Stretchable electrical devices using elastic shape memory film - Khoo, Teik Wee (2019)
This report takes on the approach to study the shape memory effects (SMEs) of a shape memory polymer (SMP) called polyethylene terephthalate (PET). The SMP is defined to have the ability to recover their original shape from their temporary deformed shape under an external stimulus such as heat. In this report, the SME of PET and the bonding of PET and raincoat are investigated in detail. The sample is first placed in a mold and heated up at a temperature higher than its glass transition temperature to get its permanent shape. It is later placed between two plates that act as constraints. It is heated up at a temperature below its glass transition temperature to get its temporary deformed shape. It is then heated again without constraints to investigate the shape recovery effects and determine if it is able to recover its permanent shape. After doing the experiment, it is shown that the PET has good shape fixity ratio and good shape recovery effect. However, it does not have a complete shape fixity ratio and shape recovery effect. The PET that has been bonded with the raincoat has a low shape fixity ratio and a bad shape recovery effect. A reason for its low shape recovery effect could be that it is hard and less elastic after being bonded together. Another reason could be that the raincoat and PET are not completely bonded as air gaps can be seen in the sample, causing the PET to be unable to recover its shape. More future research can be examined to obtain a better shape memory effect by using a more flexible material to bond with the PET. Testing different flexible material that is bonded with PET helps to investigate their SMEs and can obtain accurate result findings. Cyclic loading of RFID bonded with flexible material can be conducted.